Cathodic corrosion of Au in aqueous methanolic alkali metal hydroxide electrolytes: Notable role of water. Issue 6 (28th December 2021) - Elnagar, Mohamed M.; Jacob, Timo; Kibler, Ludwig A.
Abstract: Cathodic corrosion is an electrochemical process that induces restructuring, roughening, and etching of metal surfaces at a highly negative surface charge density, yet, details of the reaction mechanism are not fully resolved. An in‐depth fundamental understanding of the processes and parameters underlying cathodic corrosion is crucial for tailoring the surface structure of the metal electrodes and for synthesizing shape‐ and size‐controlled nanoparticles. Here, we investigate the relevance of water and hydrogen evolution in the cathodic corrosion process. To achieve this aim, Au electrodes were polarized at ‐1.6 V versus RHE in KOH and NaOH electrolytes prepared using different water + methanol mixtures. Structural changes of the Au surfaces were studied by cyclic voltammetry and monitored by scanning electron microscopy (SEM). Most importantly, cathodic corrosion does not take place in the absence of water. There is no detectable bubble formation due to the hydrogen evolution reaction on Au in purely methanolic alkali. Furthermore, the electrochemically active surface area, facet distribution, and surface morphology of Au electrodes are significantly altered upon cathodic polarization as a function of the water concentration. Cathodic corrosion features become more and more pronounced with a further increase in water content. In addition, substantial differences in the surface structure of Au are observed as a function of the nature and concentration of alkali metal cations. Overall, this study provides a more detailed understanding of the role of water and the hydrogen evolution reaction in dominating cathodic corrosion, which might advance the understanding of this phenomenon. Abstract : Metal electrode surfaces can substantially be restructured by applying highly negative potentials. The presence of water at the interface is essential to reach high surface excess charge densities in combination with strong hydrogen evolution. This is demonstrated by using various mixtures of methanol and water. The nature and concentration of alkali metal cations plays a predominant role in the nanostructuring of metal surfaces during the cathodic corrosion process.